TINGKAT EDUKASI MASYARAKAT DALAM BENTUK PEMAHAMAN TENTANG PARAMETER KEBUTUHAN JARAK DAN WAKTU ZONA RAWAN TSUNAMI PADA PROSES EVAKUASI - Mutiara Asfy Putri; Laras Oktavia Andreas; Fitra Rifwan; Faisal Ashar (Jurnal Applied Science in Civil Engineering, 2021)
Tsunami is a natural disaster that is very risky for environmental damage, for that it is necessary to mitigate the tsunami disaster in order to minimize the risk of loss, both material and moral. Tsunami disaster mitigation can be socialized through direct education so that people have knowledge about disaster mitigation to prepare themselves for saving themselves in the event of a tsunami disaster, especially in tsunami red zone areas such as Air Tawar Barat Village. On tsunami evacuation map, Air Tawar Barat Village is a potential risk area for this area because the position of Air Tawar Barat Village is ±1.4 km from the beach. In the Air Tawar Barat Village there is an Educational Institution where the agency has several buildings that can function as shelters. The distance and time needed to reach the tsunami evacuation shelter, must meet or be less than the analysis figure in order to minimize tsunami victims, for Padang City with the Golden Hours of Evacuation, it takes ± 36 minutes. After analyzing the actual time, the community must reach the nearest shelter from the beach in Air Tawar Barat Village no later than 15 minutes. From the results of the study, it can be concluded that the average level of public education in the form of understanding of the parameters of the distance and time requirements of the tsunami-prone zone in the evacuation process is 66%.